Review paper: Sonochemical degradation of volatile and Non-volatile compounds - Mukesh, Goel; Das, Ashutosh; K, Ravikumar; Ramasamy, Nagarajan (Chemenviron.net, 2012)
Destructive technologies for the wastewater treatment have significant benefits. The advanced oxidation processes (AOP) promises much in this regard. The AOP generate free radicals which act as strong oxidant to destroy the organic pollutants. AOP includes several methods such as: H2O2/UV, O3/UV and UV/TiO2. Among the above, ultrasonication is one of the less studied methods despite its unique and extreme conditions generated without using complicated and unsafe process. Ultrasonication promotes oxidative degradation of the target compound by hydroxyl radicals and also provides a possible route for thermal decomposition in the gas phase. The combination of ultrasonication and other AOP like photoxidation and ozonation substantially increases the decomposition rate of organic pollutants by increasing the amount of hydroxyl radicals required to oxidize the pollutants. The objective of this paper is to critically review the efficacy of sonolysis and its combination with other AOP on the destruction of undesirable compounds in aqueous solutions.